Method Development and Validation of Topotecan Hydrochloride in K2 EDTA Human Plasma by Using HPLC Coupled with Tandem Mass Spectrometry - Nageswara Rao, R.; Jagannath Patro, V.; Tripathy, N.K. (Asian Journal of Chemistry, 2012)
A rapid, sensitive and specific method based on high performance liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) detection with electro spray ionization in positive ionization mode has been developed for the determination of topotecan hydrochloride in K2 EDTA Human plasma. Sample preparation involved protein precipitation extraction with 0.1 % acetic acid in cold acetonitrile. chromatographic separation was performed on Agilent Eclipse XDB column (C18 150 × 4.6 mm 5μ), with a mobile phase consisting of 0.1 % acetic acid in acetonitrile and 0.5 % acetic acid in water at a flow rate of 0.7 mL/min. The analytes were then detected by monitoring the transitions m/z 422.2-219.4, 377.0 for topotecan and m/z 587.6- 124.2 for irinotecan using API-4000 LC-MS/MS system (AB Sciex). Calibration curve were linear within the range of 0.5 to 50.00 ng/mL. The lower limit of quantitation was 0.5 ng/mL. The method has been fully validated in K2EDTA Human plasma. This method can be successfully applied to the pharmacokinetic study sample analysis.